Compensation of Voltage Single-Phase SAG and SWELL Using Dynamic Voltage Restorer and Difference Per-Unit Value Method - Mohammad Sarvi; Haniyeh Marefatjou (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Recently, the demand for high power quality by customers, has increased significantly. Common power equipment to protect sensitive loads against voltage disturbances in distribution networks, which are known by D-FACTS devices include: D-STATCOM , DVR  and UPQC. Consequences resulting from industrial processes can be classified into two categories that are, nonlinear and unbalanced loads and high vulnerability to transient faults (such as voltage sag) in distribution systems. DVR is a equipment  which  was connected  in series  and  adjusting  the  loading  voltage by feeding  the  voltage  in  system. The  first  installation  was  in 1996.  usually  DVR  installed  between  sensitive loads feeder  and  source  in  distribution system. The  main  duty, fast support load  voltage (by fast detection algorithm)  during  disturbance  to  avoid  any  disconnection. In this paper approaches to compensate for voltage sag and swell as a common disturbance in voltage transmission and distribution networks is presented. A dynamic voltage restorer based on the average detection method for single-phase is discussed, in the other hand  this  paper describes the effect to using  DVR  inorder  to  restoring the voltage sag and swell by difference per-unit value method(average detection) in  distribution  system. The result of  single-phase  voltage  sag and swell simulation has been presented  by SIMULINK/ MATLAB.DOI:http://dx.doi.org/10.11591/ijece.v3i1.2134